Clinical Features and Rehabilitation Needs in Patients with Neuroinvasive West Nile Virus Infection: A Retrospective Analysis in an Area of High Incidence - Maria Chiara Maccarone; Francesco Piccione; Marina Munari; Noemi Faccin; Gianluca Regazzo; Luisa Barzon; Stefano Masiero (Applied Sciences)
Neuroinvasive West Nile Virus disease (WNND) can cause lasting cognitive and motor impairments, impacting autonomy and quality of life. Given the scarcity of research on the rehabilitative needs of patients with WNV infection, this study aims to fill a critical gap by assessing the rehabilitation needs of a real-world cohort of WNND patients. We retrospectively analyzed WNND patients who received early Physical Medicine and Rehabilitation (PMR) evaluations during the 2022 outbreak in Veneto, Italy. Data included demographics, comorbidities, length of hospital stay, days at PMR evaluation, and rehabilitation duration until discharge or death, alongside objective examination findings and Barthel Index scores. Among 29 confirmed WNND patients, the median hospital stay was 20 days, with rehabilitation starting after a median of 7 days. Motor weakness affected 48.28% of patients, swallowing issues 6.90%, and respiratory issues 24.13%. A tailored rehabilitation protocol was designed for 96.55% of patients to address functional concerns and prevent complications. Barthel Index scores showed no significant change. Discharge settings were home (58.34%), other departments (25%), and rehabilitation facilities (16.67%). This study highlights the rehabilitation needs of WNND patients, particularly regarding neuromuscular deficits, swallowing, and respiratory issues, stressing the importance of a comprehensive rehabilitation strategy for improved outcomes.